Incorporate flexibility in distribution grid planning through a framework solution. (October 2019) - Klyapovskiy, Sergey; You, Shi; Cai, Hanmin; Bindner, Henrik W.
Highlights: Comprehensive review and explanation of challenges for distribution grid planning. Analysis of existing distribution grid planning algorithms and frameworks. Generic framework streamlining planning procedure and incorporating flexibility. Practical example showing the use and value of the proposed framework. Abstract: Introduction of the distributed energy resources (DER) and new types of consumer equipment greatly increased the uncertainty in the distribution grid. Due to these changes traditional "worst case" planning algorithm from the passive distribution networks (PDN) will require extensive capital investments with a high probability that the resulted network would be largely underutilized. A prominent solution is to involve active elements (AEs) that can be found on a local level into the grid planning. A generic multi-stage planning framework for incorporating the flexibility from AEs in the distribution grid planning is proposed in this paper. The framework facilitates the transition from PDN to active distribution networks (ADN) and considers all planning stages starting from the data collection to the implementation plan. An example involving flexible demand shows how to use the framework in grid planning and demonstrates the benefits of ADN planning over PDN planning.